Artificial Intelligence in Anatomy Education - Elies Fitriani; Hanifah Hanifah; Khoirul Ima; Mahfudz Shiddiq; Miko Dharma Alrasyid; Tjahja Nurrobi (Majalah Biomorfologi, 2025)
Highlights Review of the potential use of AI in anatomy education, including any weaknesses or threats associated with integrating AI into anatomy teaching. Recommendations for incorporating AI in anatomy education within medical curricula.   ABSTRACT Background:  Artificial intelligence (AI) refers to machines capable of performing human tasks and exhibiting intelligent behavior. The application of AI in medical education has increased significantly, especially during the COVID-19 pandemic, as remote teaching became widespread across all medical disciplines, including anatomy. Objective:  This narrative review aimed to explore the potential use of AI in anatomy education and to identify any associated weaknesses or threats related to its integration. Material and Method: A systematic literature search was conducted using PubMed and Embase (limited to the past 5 years), and Google Scholar (limited to the past 2 years), employing keywords related to "artificial intelligence" and "anatomy education". Inclusion criteria were randomized controlled trials and review articles focusing on AI tools in anatomy education, published in English and freely accessible. Exclusion criteria included abstract-only publications, non-human studies, and studies not specifically related to anatomy education. Of the 3,298 articles identified, seven met the inclusion criteria. Result:  Seven articles fulfilled the inclusion criteria. The reviewed literature explored AI applications in anatomy education, highlighting innovations such as blended learning, automated assessments, and digital platforms. Overall, AI demonstrates potential to improve teaching effectiveness and student engagement. However, successful implementation requires strategic planning, adequate infrastructure, and a solid pedagogical framework. Conclusion:  AI has emerged as a valuable tool in anatomy education, enhancing learning outcomes, accessibility, and instructional flexibility. Nonetheless, its integration must be carefully managed to overcome current limitations and ensure equitable, effective, and sustainable educational practices.